ANALISA PENGEMBANGAN E-LIBRARY SMK MA’ARIF BANYUMAS SEBAGAI MEDIA TATAKELOLA PERPUSTAKAN - Nurrohma, Siti; Idris, Muhammad (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
The development of the SMK Ma’arif Banyumas is a very important requirement for library staff. The purpose of this writing is to produce an application that can facilitate library employees to carry out loan register and return to the library of SMK Ma’arif Banyumas. This application is a mobile application built with androi. The methodology used to build an application is the methodof observation, interviews and literature. While the one used for system development is waterfall, in this study resulted in a mobile-based library application system that can be used by library staff SMK Ma’arif Banyumas. It is expected that the existence of this system can facilitate library staff to register and borrow books at the SMK Ma’arif Banyumas in order to be more accurate and more structured to borrow and return.